2014
DOI: 10.2139/ssrn.2414370
|View full text |Cite
|
Sign up to set email alerts
|

Making the Case for Directed Organ Donation to Registered Donors in Israel

Abstract: Background: The number of deceased donor organ donations in Israel is lower than average when compared to other Western World countries. To address the organ gap, the 2008 Organ Transplantation Law provides new interventions, including important incentives to donors (and their families). The most notable of these was granting priority to registered donors (i.e., people on the waiting list who signed a donor card). The current study presents the normative arguments as well as the first documentation of public a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
1
1
Order By: Relevance
“…An additional notable finding is that, though Israel's organ allocation policies prioritize registered donors, presumably as a means of encouraging donation, respondents (including registered donors) ranked donor status as the least important criterion in allocation decisions. This result diverges from outcomes obtained in surveys in Israel [7, 31,33] as well as in other countries, in which respondents indicated that priority ought to be given to registered donors (in spite of the fact that their countries of origin do not prioritize on this ground [15,39]). Nevertheless, it is important to note that when confronted with hypothetical trade-off scenarios, respondents did choose, in some cases, to prioritize a registered donor over a candidate who had not registered as a donor.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…An additional notable finding is that, though Israel's organ allocation policies prioritize registered donors, presumably as a means of encouraging donation, respondents (including registered donors) ranked donor status as the least important criterion in allocation decisions. This result diverges from outcomes obtained in surveys in Israel [7, 31,33] as well as in other countries, in which respondents indicated that priority ought to be given to registered donors (in spite of the fact that their countries of origin do not prioritize on this ground [15,39]). Nevertheless, it is important to note that when confronted with hypothetical trade-off scenarios, respondents did choose, in some cases, to prioritize a registered donor over a candidate who had not registered as a donor.…”
Section: Discussioncontrasting
confidence: 89%
“…We note that several studies have previously been conducted in Israel to shed light on various aspects of the public's perception of organ donation. These studies investigated the attitudes of a specific group towards organ donation (college students [29]; the Zionist ultraorthodox community [30]), examined public thoughts about directed organ donation to registered donors [31], studied the impact of particular personality variables on willingness to become an organ donor [32], explored factors that encourage or inhibit organ donation [7] or surveyed willingness to donate in exchange for prioritization in organ allocation [33]. In contrast to these studies, the current study focuses on the preferences and values of Israel's Jewish population with regard to different aspects of the current organ allocation policy.…”
Section: Introductionmentioning
confidence: 99%